An assessment of a Western blot method for the investigation of canine cutaneous adverse food reactions. Issue 3 (6th April 2018) - Maina, Elisa; Matricoti, Irina; Noli, Chiara
Abstract : Background: Adverse food reaction (AFR) is diagnosed with a two month elimination diet (ED), followed by challenge with the original food. Hypothesis/Objectives: To evaluate reactivity of selected EDs and performance of a Western blot serological test for the diagnosis of AFR. Animals: Twenty five food reactive (FR) and 13 non food reactive (NFR) privately owned dogs. Methods: Sera were tested for antibodies against hydrolyzed poultry feather (RCA), hydrolyzed soy (PHA), hydrolyzed fish (FUH), limited antigen horse and potato (THP), fresh horse meat and the offending food for each FR dog as documented by provocative challenge. Results: Fourteen sera were negative and two positive to all foods. Sera from five of 13 NFR and three of 25 FR dogs were reactive to hydrolyzed foods. The RCA diet was recognized by four of 38, FUH by six of 38 and PHA by one of 28 samples. THP was recognized by 14 of 33 and fresh horse by one of ten dogs that had never eaten horse meat. The test correctly identified one of 15 dogs allergic to FUH. Twenty of 25 FR sera were negative for the dogs' respective offending foods (20% sensitivity), whereas four of 13 NFR sera were positive to the dogs' usual diets (69% specificity). Conclusion and clinical importance: Western blot analysis cannot be considered as a valid tool for the diagnosis of AFR; it may serve as an aid in selecting an ED. Abstract : Background – Adverse food reaction (AFR) is diagnosed with a two month elimination diet (ED), followed by challenge with the original food.Hypothesis/Objective – To evaluate reactivity of selected ED and performance of a Western blot serological test for the diagnosis of AFR.Conclusion – Western blot analysis cannot be considered as a valid tool for the diagnosis of AFR; it may serve as an aid in selecting an ED.